2013
DOI: 10.1186/1471-2288-13-132
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of acute stroke unit care: What’s beyond the statistical significance?

Abstract: BackgroundThe benefits of stroke unit care in terms of reducing death, dependency and institutional care were demonstrated in a 2009 Cochrane review carried out by the Stroke Unit Trialists’ Collaboration.MethodsAs requested by the Belgian health authorities, a systematic review and meta-analysis of the effect of acute stroke units was performed. Clinical trials mentioned in the original Cochrane review were included. In addition, an electronic database search on Medline, Embase, the Cochrane Central Register … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 17 publications
1
23
1
8
Order By: Relevance
“…This finding confirms the link between GDP and mortality after cerebral infarction and shows that the results of Sposato and Saposnik (2012) are valid at the regional level as well. Many studies have shown that primary and comprehensive stroke units have lower mortality (Sun et al, 2013), but this finding was not replicated in this regional-level analysis. At the national level, benchmarking of healthcare providers has become increasingly common (Oderkirk et al, 2013).…”
Section: Discussioncontrasting
confidence: 69%
“…This finding confirms the link between GDP and mortality after cerebral infarction and shows that the results of Sposato and Saposnik (2012) are valid at the regional level as well. Many studies have shown that primary and comprehensive stroke units have lower mortality (Sun et al, 2013), but this finding was not replicated in this regional-level analysis. At the national level, benchmarking of healthcare providers has become increasingly common (Oderkirk et al, 2013).…”
Section: Discussioncontrasting
confidence: 69%
“…The organized inpatient care (stroke unit) is an approach to stroke patients that has shown superiority compared to other approaches (Nimptsch & Mansky, 2014). The core characteristics of stroke unit settings are multidisciplinary staffing (medical, nursing, and therapy staff-usually including physiotherapy, occupational therapy, speech therapy, and social work) and coordinated multidisciplinary team care incorporating meetings at least once a week (Sun, Paulus, Eyssen, Maervoet, & Saka, 2013).…”
mentioning
confidence: 99%
“…Patients who had been treated in the stroke unit are more likely to survive, return home, and regain independence (Sun et al, 2013;Weder, 2015). Using the stroke unit model with interdisciplinary teams is more effective at treating stroke than aspirin/thrombolysis/statin use and lowering blood pressure (Langhorne, de Villiers, & Pandian, 2012).…”
mentioning
confidence: 99%
“…Identified limitations to an effective implementation include lack of knowledge of the benefits of stroke units, financial barriers, insufficient staffing, lack of protocols and of collaboration between professionals. 29 Likewise, in Lithuania there is no formal requirement to have an organized stroke unit, or formal certification to provide stroke care. Compared with other European countries, Lithuania had higher incidence of stroke, higher prevalence of hypertension and atrial fibrillation, 4 and a poor outcome after stroke.…”
Section: Discussionmentioning
confidence: 99%